Experimental fracture healing with external skeletal fixation in a pigeon ulna model - Tunio, Ahmed; Jalila, Abu; Meng, Coh Yong; Shameha, Intan (Journal of Advanced Veterinary and Animal Research, 2014)
This study was conducted to assess the healing of transverse ulna fracture when fixed with external skeletal fixation (ESF) in pigeon. Ulna fracture was created under Isoflurane anesthesia in pigeons. A total of 12 pigeons were used in this study, and they were divided into three equal groups: Group-1, Group-2 and Group-3. The birds of the three groups were sacrificed at 3, 6, and 12 weeks after successful fracture surgery. It was found that bone union occurred between three and six weeks in all groups. Bone alignment, and callus remodeling were evident at 12 weeks (p<0.05) post fracture fixation. There were no radiographic evidence of callus remodeling in any bird at 3 and 6 weeks post-surgery. The radiographic observations of fracture healing in this study have confirmed that ESF fixation is an effective method to stabilize ulna fracture in pigeons and results in faster fracture healing. DOI: http://dx.doi.org/10.5455/javar.2014.a14 J. Adv. Vet. Anim. Res., 1(2): 58-64, June 2014